Human Platelet Lysate Media Supplement Supports Lentiviral Transduction and Expansion of Human T Lymphocytes While Maintaining Memory Phenotype - Emanuele Canestrari; Hayley R. Steidinger; Brianna McSwain; Steven J. Charlebois; Christina Tenenhaus Dann (Journal of Immunology Research)
Immune cell therapy has emerged as a promising approach to treat malignancies that were up until recently only treated on a palliative basis. Chimeric antigen receptor- (CAR-) modified T lymphocytes (T cells) in particular have proven to be very effective for certain hematological malignancies. The production of CAR T cells usually involves viral transduction and ex vivo culture of T cells. The aim of this study was to explore the use of human platelet lysate (HPL) compared to two commonly used supplements, human AB serum (ABS) and fetal bovine serum (FBS), for modified T cell production. For studying transduction, activated T cells were transduced with lentivirus to deliver GFP transgenes with three different promoters. Transduction efficiency (percent GFP) was similar among the supplements, and a modest increase in the transgene product (mean fluorescence intensity) was observed when HPL was used as a supplement compared to ABS. To study the effect of supplements on expansion, peripheral blood mononuclear cells (PBMCs) were activated and expanded in the presence of interleukin 2 (IL2) for fourteen days. T cell expansions using HPL and ABS were comparable and slightly less than the expansion obtained with FBS. Interestingly, cells expanded in media supplemented with HPL showed a higher percentage of T cells with a central memory phenotype compared to those expanded in ABS or FBS. Protein profiling revealed that the phenotypic differences may be explained by elevated levels of several cytokines in HPL, including IL7. The results suggest that the use of HPL as a cell culture supplement during the production of modified T cells is a reasonable alternative to ABS. Furthermore, the use of HPL may enhance in vivo performance of the final product by enriching for central memory T cells that are associated with long-term persistence following adoptive transfer.